Increasing of Breast Milk Production Before and After Back Acupressure and Correnct Baby Positions-Latch on - Nurul Pujiastuti; Agus Setyo Utomo; Mustayah Mustayah (Humanistic Network for Science and Technology (HNST), 2023)
Mothers often experience the problem of a lack of milk production due to malnutrition or malnutrition, working mothers, sore nipples, only a small amount of milk coming out or disturbed mental peace. The Ministry of Health or the Republic of Indonesia targets exclusive breastfeeding up to 80%. One effort to increase milk production is by doing complementary therapies that affect milk production, for example back acupressure. The purpose of this study was to identify increased milk production in breastfeeding mothers before and after back acupressure and baby positions-latch on. This study was a case report, involving 3 breastfeeding mothers. Data were collected through interviews and observation. The results of the study showed that there was an increase in milk production after acupressure was performed on the scapula and T1-T6 area for two weeks (twice a week) combined with the correct positioning of the baby. Before the procedure, the milk production was between 80-120 ml and after the procedure, the milk production was between 95-125 ml. Back-squat and baby-attachment positions can increase milk production in nursing mothers. It is hoped that breastfeeding mothers can increase milk production through back acupressure combined with the correct positioning of the baby. Keywords: back acupressure; breast milk production; baby positions-latch on